Pertimbangan Saddu Dzari’ah dalam Permohonan Izin Poligami: Studi Kasus Penetapan Nomor 886/Pdt.G/2022/PA.Ta - H. M Isbat Atiqillah Pranata; Rani Nur Azizah (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
Law No. 1 of 1974 on Marriage in the Republic of Indonesia sets forth the conditions for granting permission for polygamy, specifically outlined in Article 4(2) and Article 5. In the court decision No. 886/Pdt.G/2022/PA.Ta, the judges granted the petition for polygamy despite the applicant’s failure to meet the legal requirements stipulated in Article 4(2). Moreover, the panel of judges expressed concern regarding the applicant’s financial incapacity to support two households, as his income was below the regional minimum wage (UMK) of Tulungagung Regency. This study aims to analyze the court’s decision using the Saddu Dzari'ah approach, assessing both the implications had the petition been granted or denied. The research employs a normative juridical method, using both case-based and conceptual approaches. Data were analyzed qualitatively through five stages: verification, organization, editing, analysis, and conclusion drawing. The findings indicate that applying the Saddu Dzari'ah approach reveals the presence of mafsadat (harm) regardless of whether the petition is granted or denied. However, the degree of harm differs: granting the petition would result in qath’i (definite) mafsadat. Thus, rejecting the petition aligns more closely with the Saddu Dzari'ah principle, as it mitigates greater harm by choosing the lesser evil.